THE SYSTEM OF ENTITIES USING INFORMATION TECHNOLOGIES IN THE FIELD OF LIFE SAFETY: ADMINISTRATIVE, LEGAL AND ECONOMIC PRINCIPLES OF EFFECTIVE FUNCTIONING - Dmytro Bondar (Baltic Journal of Economic Studies)
The present article undertakes a study of the system of subjects using information technologies in the field of life safety, namely administrative law and economic principles of their activities. It also identifies promising areas for improving the current national legislation which regulates relevant legal relations. It is noted that the system of civil protection subjects is generally defined by the Code of Civil Protection of Ukraine. However, in light of the escalating natural, man-made, social and military threats, there is an imperative to establish a unified information and telecommunications system for civil protection. This system should encompass an interactive map and a database of civil protection subjects. It is imperative to establish a definitive legal framework encompassing the utilisation of information technologies in life safety contexts. This framework is crucial for the effective administration of pertinent information and telecommunications systems, as well as the maintenance of associated databases. Concurrent maintenance of mobile applications, designed for the mobilisation of human and material-technical resources in the event of a threat or the immediate occurrence of an emergency, is also paramount. The author concludes with a call for amendments to be made to the current national legislation on the administrative law regulation of mobile application usage in the field of life safety. This would include the rights and obligations of subjects that will administer the aforementioned mobile applications and subjects that will be involved in the elimination of emergencies and their consequences as volunteers via the installed mobile application. Particular attention is paid to the need for proper technical support of entities involved in the elimination of emergencies and their consequences with the help of information technology.